Clinical Evaluation of Topical Metronidazole and Chlorhexidine Gel following Scaling and Root Planing in Patients with Chronic Periodontitis - Acharya, Pujan; Kumar, Manoj; Saimbi, CS (Journal of College of Medical Sciences-Nepal, 2019)
Background: Chronic periodontitis is the most prevalent form of periodontitis with a multifactorial etiology, dental plaque being the primary etiologic agent. The removal of such etiologic factor through scaling and root planing builds the foundation of treatment. In addition, the use of an antimicrobial adjunct augments elimination of microbes leading to subsequent control of the disease. Chlorhexidine and Metronidazole have been found to be active against several periodontopathogens. In this study, the use of these antimicrobial gels has been made. To evaluate and compare the clinical efficacy of subgingival application of 1% Metronidazole, 1% Chlorhexidine and Combination gel when used as an adjunct to non-surgical therapy. Methods: A total of 120 patients, age group 30-60 years with chronic generalized periodontitis were included in the randomized, controlled, double blinded study. The patients were randomly divided into four groups and treated with scaling and root planing along with antimicrobial adjunct. The antimicrobials used were Chlorhexidine, Metronidazole, Combination of Chlorhexidine and Metronidazole, and Placebo. Clinical parameters (plaque index, gingival index, probing pocket depth and clinical attachment level) were recorded at baseline, 1 month and 3 months. Results: In all the groups, there was a statistically significant reduction in all the clinical parameters at different time intervals. Inter-group comparison with respect to clinical changes showed that Combination gel was the best. Conclusions: Long term, controlled randomized trials with more samples are suggested to further validate the efficacy of these antimicrobial drugs.